The Quality of Accounting Information: Relevance or Value-Relevance? - Nasrin Azar; Zarina Zakaria; Noor Adwa Sulaiman (Asian Journal of Accounting Perspectives, 2019)
Research aim: This paper critically evaluates the qualitative characteristics of accounting information that can be drawn from the Financial Accounting Standard Board (FASB)/International Accounting Standard Board (IASB) Conceptual Framework and Value-Relevance studies that are motivated by users of accounting information.